Implementation of Legal Aid by the Local Government (Case Study of the Local Government of Jember Regency) - Syahara, Tiara Putri (Faculty of Law Universitas Negeri Semarang, 2021)
Basically, the right to obtain defense from an advocate or public defender (access to legal counsel) is a human right of all people and is one of the elements to obtain justice for everyone. However, in reality, local governments generally only provide legal assistance on a non-litigation basis where its implementation does not burden the regional budget at all. Based on this, the researchers made two problem formulations, namely 1). How to protect the community through the provision of legal aid and 2). How is the implementation of the provision of legal aid by the local government? The author uses a normative juridical research approach. From the results of the study, it was found that the provision of legal aid is not only regulated in the Constitution but is also regulated in the regulations below it up to the Regional Regulation level. Local governments can allocate funds for the implementation of legal aid in the APBD.